"Contribution à l’étude expérimentale d’humidité de sol dans l’irrigation par planches sous les conditions arides (Cas d’Ouargla)" - عبد اللطيف, بن عمر; خالدي, غرمولي; كمال, حدد (University of El-Oued, 2022)
"The purpose of our contribution to this study is to study the soil moisture in earthen or bed irrigation under dry circumference to control and monitor the moisture of the land, which improves and determines the water needs. of the plant, which results in increased plant activity, abundant yields, high quality and many other advantages. " الهدف في مساهمتنا في هذي الدراسة هو دراسة رطوبة التربة في الري الأرضي او اللوحي تحت ضرف جاف وذلك للتحكم في الرطوبة للأرض ومراقبتها مما يحسن ويحدد احتياجات النبات للمياه مما ينتج عنه نشاط متزايد للنبات وعائدات محاصيل وفيرة وجودة عالية والكثير من الإيجابيات الأخرى
مذكرات ماستر تخصص ري
Keywords: soil moisture, logistic irrigation, dry conditions; "رطوبة التربة ,الري اللوحي, ظروف جافة. "